Curriculum Development Innovations of Islamic Education Subject at SMA Negeri 3 Parepare - Anwar Sewang (Ta'dib: Jurnal Pendidikan Islam, 2022)
The research aimed to analyze curriculum development innovations in the implementation of Merdeka Belajar Curriculum in the subject of Islamic Education at SMA Negeri 3 Parepare. The research used a qualitative approach with case study design. The data were collected by interviewing the principal, vice principal of academic affairs, and an Islamic Education teacher, having observation, and getting documentation. Then, the data collected were analyzed by using interactive analysis model. The research results showed that that curriculum development innovations of the Islamic Education at SMA Negeri 3 Parepare on the basis of the Merdeka Belajar Curriculum were: 1) intracurricular through Islamic Education as a subject; 2) intracurricular through integration in other subjects; and 3) the activities of the Pancasila Student Profile Strengthening Project. These three activities were supported by extracurricular activities, namely Islamic studies, Friday charity, Duha prayers, Zuhr prayers, and commemoration of Islamic holidays